(untitled) (Research, Society and Development, 2021)
Considering the importance of nursing professionals in the organization and management of care, the aim of this study was to map the scientific production in a database on studies reporting possible challenges of nursing working in epidemiology in coping with Covid-19, having based on the protagonism of Brazilian authors. Descriptive bibliometric study extracted from the Web of Science database, with a database organized in Microsoft Excel 2019 and analysis using the VOSviewer® software (version 1.6.16). 231 original articles (78.5%) and 63 (21.5%) review articles were found, with a predominance of the United State of America (27.8). The periodicals make up the A stage of Capes, in almost its entirety. The Brazilian production of the subject in question, when compared to publications from other countries, proved to be insufficient to meet the current demands of nursing activities in epidemiology. In summary, a relevant volume of publications that contemplate the epidemiological aspect centered on the care processes of nurses and a low volume on specific actions of nursing performance in epidemiology.